Studies on phenotypic stability in sesame (Sesamum indicum L.): Studies on phenotypic stability in sesame (Sesamum indicum L.) - A P T RAJKAPUR HARTIABINESARAJA; S T PONSIVA; S PRAVEENKUMAR; S THIRUGNANAKUMAR (Journal of Oilseeds Research, 2020)
Sixty genotypes of sesame were studied for phenotypic stability over three season. Genotypes season interaction was significant for all the traits except plant height at maturity. Maximum phenotypic expression for plant height, number of branches, no. of capsules, seed length, seed breadth and oil content was observed in SI. For days to maturity, number of flowers, 1000 seed weight, 1000 seed volume, seed yield and harvest index the maximum expression was observed in SIII, capsule volume, number of seeds/capsule, seed density and total dry matter production displayed maximum expression. Genotype x seasonal interaction was significant for all the traits except plant height at maturity indicating that different genotypes responded differently to changes in the season. The genotype x season interaction component was predominant for 100 seed weight, seed breadth, capsule volume, number of seeds per capsule, number of branches, harvest index, total dry matter production, oil content, seed yield, days to maturity, number of flowers and number of capsules. For plant height and 1000 seed volume, genotypic component of variation(2g) was greater than the genotype x season component ( 2g1) indicating that these two characters were least sensitive of seasonal changes compared to other characters. A major portion of the variance attributed to genotype x season interaction was accounted for by the linear component (variance due to regression) for all the traits excepting capsule volume and total dry matter production. For capsule volume the linear and non- linear component was almost equal. For total dry matter production, linear component was less than the non-linear component. Preponderance of linear portion over non-linear portion was suggestive of possibilities of prediction of the performance of the genotypes across the seasons. 1000 seed volume followed by plant height, days to maturity and 1000 seed weight were the most predictable one.